Blockchain-based trusted traceability and sustainability certification of leather products - Ruba Islayem; Haya R. Hasan; Ahmad Musamih; Khaled Salah; Raja Jayaraman (PLoS ONE, 2025)
The leather supply chain comprises numerous organizations and stakeholders, particularly when sustainability aspects are taken into account, making it a complex system. The complexity inherent in such systems can lead to inaccurate information, lack of transparency, and limited data provenance. Moreover, there has been a surge in the call for sustainable practices within leather production, propelled by growing environmental consciousness and ethical considerations. In this paper, we address these challenges by proposing a blockchain-based solution designed to ensure trusted and secure traceability and sustainability throughout the entire life cycle of leather products. By harnessing the inherent capabilities of Ethereum smart contracts and blockchain technology, such as decentralization, immutability, data integrity, and transparency, we guarantee the secure and reliable tracing of materials from the farm to the final consumer. Moreover, we provide proof of sustainability by which certification agencies monitor, audit, and approve the sustainable processes and practices carried out by the different stakeholders at all stages of production to ensure compliance with industry standards and regulations. The paper presents the blockchain-based system architecture, implementation, and validation of algorithms and smart contracts. It also evaluates the security measures and cost-effectiveness of the system to offer valuable insights into its robustness and efficiency. We have made the developed smart contracts code publicly available on GitHub.